FACTOR ANALYSIS OF DIABETES MELLITUS MANAGEMENT IN RURAL AREA AND URBAN AREA - Anita Fatarona; Pranata, Andi Eka (Journal of Islamic Nursing, 2023)
Introduction. Fluctuations in blood sugar levels greatly affect the health status of diabetes mellitus sufferers. Blood sugar stability that is difficult to achieve causes significant health problems. One of the things that diabetes mellitus sufferers must pay attention to is the pattern of maintaining health through diabetes mellitus management itself. Aims: This study aims to determine the factors that influence diabetes mellitus management patterns. Methode: This type of research is descriptive with a cross sectional approach. The population in this study were diabetes mellitus sufferers. The number of samples in this study were 60 respondents. Data collection was carried out using a questionnaire to measure motivation, perception, and spirituality. Statistical analysis using linear Chi-Square analysis. The inclusion criteria in this study were pre-diabetes mellitus sufferers who lived in rural areas and urban areas of society. the exclusion criterion is not willing to be a respondent The results of this study show that there is a relationship between motivation, perception, adaptation and spiritual factors in the management of diabetes mellitus results of data analysis p value <0.05, so it can be concluded that self-perception, self-motivation, coping skills, and spirituality affect the management of diabetes mellitus.